Inulin determination of yam bean tuber (Pacyrrhizus erosus l.) water extract from different altitude areas using TLC- Densitometry - Yuni Retnaningtyas; Lestyo Wulandari; Mariska Wimala (Pharmaciana, 2022)
Inulin is a polysaccharide with a lot of potential in the field of food and pharmaceuticals. Inulin can be found in yam bean tuber. Chemical constituents of yam bean tuber are inulin, pachyrion, and rotenone. The levels of inulin could be influenced by differences in the altitude of the cultivation area. The objective of this study was to determine the inulin of yam bean tuber extract from several areas in East Java based on the altitude difference, they are low (Gresik), middle (Kediri), and high (Malang), using validated TLC Densitometry method. The samples were extracted by the infusion method. The samples were put to silica gel TLC plates and developed using ascending chromatography with a mobile phase of 0.5:7:2 glacial acetic acid: methanol:  deionized water.  Densitometry at 380 nm was used to assess the intensity of inulin spots dipped in Aniline: diphenylamine: phosphoric acid (5:5:1), and winCATS software version 1.3.0 was used to quantify the results. A standard curve  meets the requirement of linearity (r=0.997; Vxo=3.847%), sensitivity (LOD=71.030 ng/spot, and LOQ=236.766 ng/spot), selectivity and specificity, Precision (RSD≤2.754 %), and accurate (% recovery ± RSD = 100.161 ± 1.839%). The results showed that the inulin content in yam tubers produced by areas with different altitudes had different inulin levels. The levels of inulin derived from the low altitude (Gresik) was 9.066 ± 1.218 %, middle (Kediri) was 7.776 ± 0.420 %, and high (Malang) was 6.796 ± 2.045 %. One-Way ANOVA test showed the significant difference between the levels of inulin from different altitude areas (p < 0.01), the highest inulin level comes from yam bean tuber from low altitude.